METODE UPWIND DIFFERENCING UNTUK MODEL PERUBAHAN TEMPERATUR PADA ALAT PENDINGIN UDARA DARI PEMBANGKIT TENAGA DIESEL - , Dra. Endang Mawarsih ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The advection/convection equation had more application in engineering technical sector one of them is for analyzing the temperature exchange at charger air cooler model from diesel power plant. In this case the upwind differencing method was used to solve the numerical finite difference that was used to examine the stabilities methods and the certainly that iteration can be convergenced to fix constant value condition to speed up convergence by using values of dirichlet boundary condition as initial value from iteration. The fin with aluminium material at charger air cooler was for cooling air from iteration on 70% as natural. The turbulent flow was leaded from force of aerodymics in the fin and air, as a result the air temperature reached the constant convergence.